Likely substantial underestimation of reported methane emissions from United Kingdom upstream oil and gas activities. Issue 1 (22nd December 2022) - Riddick, Stuart N.; Mauzerall, Denise L.
Abstract : The United Kingdom government's National Atmospheric Emissions Inventory, used to provide UK greenhouse gas emission data to the United Nations Framework Convention on Climate Change, underestimates UK emissions from upstream oil and gas activities by approximately 80%. Abstract : The United Kingdom (UK) government's National Atmospheric Emissions Inventory (NAEI) is used to provide UK greenhouse gas emission data to the United Nations Framework Convention on Climate Change. The NAEI bottom-up approach estimated 2019 methane (CH4 ) emissions from the extraction and transport of oil and natural gas (O&G) from offshore sources to onshore terminals at 52 Gg CH4, corresponding to the loss of 0.14% of gas production. Here we investigate the approaches used by the NAEI and find it substantially underestimates leakage. We suggest alternative integrated approaches that combine direct measurements, management practices, and the effects of environmental conditions to estimate fugitive emissions. We estimate the total UK CH4 emissions from flaring, combustion, processing, venting, and O&G transfer to be 289 Gg CH4 (0.72% of production), five times larger than the NAEI estimate. We suggest NAEI underestimates emissions because of outdated/incorrect emission factors, incomplete activity data, and incomplete data on vented emissions. Similarly, CH4 emissions from upstream O&G in other countries may be underestimated, with regional regulatory differences resulting in venting often being a substantially underestimated emission source. While bottom-up methods can be used to understand the relative size of emissions from the extraction and transport of O&G, they are inherently biased low as they only include emissions from processes and activities designated as emission sources and for which emission factors exist. Emission factors remain a large source of uncertainty as many used to generate the NAEI inventory are taken from industrial studies or unpublished research that have not been independently validated. To improve the NAEI estimate, widespread and frequent direct measurements are needed to supplement and improve bottom-up emission estimates generated with existing emission factors and activity levels.